A close look at citizen science as an extension of science: Actor network theory study of the three large scale Environmental Citizen Science Projects in Turkey - Us, Hilal (Social Sciences Institute, 2020)
Citizen Science in other words Public Participation in Scientific Research has been flourishing in intersections of academia, civil society and policy making by becoming an extension of science and a subject of Science, Technology and Society Studies (STS). Citizen science literature has been developing with the considerations on research types, motivations, benefits and shortfalls of citizen science. This thesis carries an actor network theory approach and problematizes by considering the citizen science literature, how the three frequent type citizen science researches in Turkey which are ‘The Turkish Breeding Bird Atlas’, ‘The Map of Threats to Water Resources in Turkey’ and ‘The National Jellyfish and Gelatinous Organisms Watch Program’ have been constructed as an extension of science. In order to describe the research processes, qualitative multiple case study was conducted, thirteen semi-structured interviews were made with the project coordinators of the three projects and the active citizen scientists of the two projects. The interviews and the projects’ documents were analyzed with NVivo through using Michel Callon’s (1984) four moments of translation (problematization, interessement, enrolment, mobilization) and the themes of citizen science such as motivations, benefits, shortfalls and science.
Bilimin bir uzantısı olarak vatandaş bilimine yakından bir bakış: Türkiye'deki üç büyük ölçekli Çevresel Vatandaş Bilimi Projesinin aktör ağ teorisi çalışması
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 2020
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2020
Keywords: Citizen science